INTERAKSI SIMBOLIK PADA PERCERAIAN AKIBAT MEDIA SOSIAL FACEBOOK: STUDI KASUS PENGADILAN AGAMA KOTA CIMAHI - Rizqi Ikhsani Faradila; Ira Lusiawati (KOMUNIKA BANGSA, 2026)
The use of Facebook social media is involved in a dynamic relationship between married couples that can result in a conflict that leads to the decision to divorce. Through in-depth interviews with the parties involved in the divorce, participatory observation, and analysis of court documents, the study found that symbolic interactions on Facebook, such as private conversations, comments, and public posts, often trigger mistrust, jealousy, and conflict that leads to divorce. The findings also show that the impact of Facebook use is not only limited to individual relationships but also affects social perceptions of marriage and divorce. The results of this study are expected to provide a deeper understanding of the negative impact of social media on marriage relationships, as well as suggest more effective prevention strategies to reduce the rate of divorce due to social media in the community.